2014
DOI: 10.2166/wst.2014.013
|View full text |Cite
|
Sign up to set email alerts
|

Biofilter design for effective nitrogen removal from stormwater – influence of plant species, inflow hydrology and use of a saturated zone

Abstract: The use of biofilters to remove nitrogen and other pollutants from urban stormwater runoff has demonstrated varied success across laboratory and field studies. Design variables including plant species and use of a saturated zone have large impacts upon performance. A laboratory column study of 22 plant species and designs with varied outlet configuration was conducted across a 1.5-year period to further investigate the mechanisms and influences driving biofilter nitrogen processing. This paper presents outflow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 12 publications
3
60
1
2
Order By: Relevance
“…This difference may in part reflect a design change towards media with a high sand and low nutrient content, which minimises nutrient leaching [9], [26]. However, the current results do require validation under field conditions and extension by tracing nitrogen fate over longer periods.…”
Section: Discussionmentioning
confidence: 99%
“…This difference may in part reflect a design change towards media with a high sand and low nutrient content, which minimises nutrient leaching [9], [26]. However, the current results do require validation under field conditions and extension by tracing nitrogen fate over longer periods.…”
Section: Discussionmentioning
confidence: 99%
“…O bom desenvolvimento da macrófita provavelmente está relacionado à saturação do maciço filtrante, o qual disponibilizou maior umidade ao meio. Estudos com ensaios em colunas simulando filtros biológicos com variáveis de projeto, incluindo espécies de macrófitas e zonas saturadas, concluiu que a inclusão de uma zona saturada em filtros biológicos tem grande importância para as macrófitas, na proteção das mesmas contra a variabilidade climática, principalmente relacionada à disponibilidade hídrica [20]. Além da adaptação e do desenvolvimento, as macrófitas também se apresentaram resilientes em relação à presença de plantas invasoras e infestação de afídeos.…”
Section: Resultsunclassified
“…2), which promote uptake of nutrients, enhance microbial activity in the root zones and contribute DOC for denitrification [4244]. A timeline showing the development of bioretention systems is provided in Fig.…”
Section: Applications Of Denitrifying Wood Chip Bioreactorsmentioning
confidence: 99%
“…Several studies have compared bioretention systems with and without plants and found that generally, systems with plants perform better at removing nitrogen than systems without plants [42, 44, 71, 72]. Studies have observed how plant species along with the organic content in the media of the bioreactor and the use of an IWSZ influence the variation of nitrogen removal.…”
Section: Process Microbiologymentioning
confidence: 99%